Malayssian's Perception In Mobile Commerce - Mah, Kwang Yih (2006)
This study is an early attempt to provide empirical data on Malaysian's perception in mobile commerce. A review of the literature has been carried out mainly in the area of mobile commerce environment, mobile commerce value chain, and other related successful real case studies.